Concern, Conception, and Consequence: Re-thinking the Paradigm of Higher Education in Dangerous Times - Sterling, Stephen (Frontiers in Sustainability, 2021)
Discussion of the role of universities in relation to broad issues of sustainability has been current for some decades, although predominantly at the margins of debate and policy. Yet a recent rapid rise of concern - catalysed by mounting evidence of climate crisis, biodiversity loss, pandemic disease and further systemic issues -is focussing renewed attention on the adequacy of the response of higher education to unprecedented times of urgency, uncertainty and threat. Whilst it is now widely acknowledged that the fate of the planet and of humanity hangs in the balance, there still remains an astonishing disconnect between pressing signs of global change, and the relatively closed world of higher education. A trend towards greening universities’ operations is positive, but fails to engage or galvanise the cultural and value shift towards a holistic and ecological zeitgeist that is now necessary to generate widespread institutional systemic change. This paper delves into deep causal factors that have historically impeded the ability of universities to respond fully and effectively to present and probable future realities, pointing to the foundations of Western thought such as reductionism, objectivism, dualism, individualism, anthropocentrism, rationalism, instrumentalism and technocentrism that shape mainstream education policy and practice, overlain and reinforced in more recent times by neo-liberal conceptions of the purpose of universities in a modern economy. It is argued that these elements of our culturally shared worldview constrain our ability to perceive and respond deeply, fully and wisely to the global predicament, but also maintain destructive patterns of development. Whilst there is increasing acceptance that education must “transform” in order to - in turn - be transformative in effect, there is less clarity about the guiding assumptions and ideas that inform mainstream policy and practice, and about the philosophic value bases that can facilitate transformative educational thinking, policy and practice. A framework of three broad and complementary components of paradigm - Concern, Conception and Consequence - is employed to outline the shape of the systemic paradigmatic shift that universities need to urgently navigate in order to maximise their ability to respond fully to contemporary socio-economic and ecological conditions and trajectories.